Utilization of rock phosphate by crops on a representative toposequence in the northern Guinea savanna zone of Nigeria: response by maize to previous herbaceous legume cropping and rock phospate treatments - Vanlauwe, Bernard; Diels, J.; Sanginga, P.; Carsky, R.J.; Deckers, J.; Merckx, Roel (Elsevier, 2000)
Mucuna pruriens and Lablab purpureus can immediately benefit from rock phosphate (RP), but as both herbaceous legumes have only limited economic value, these benefits are only meaningful if yields of a subsequent maize crop are improved. The impact of RP application to Mucuna and Lablab on grain yield, total N, and total P uptake of a subsequent maize crop was evaluated for a set of non-acidic soils on a representative toposequence (‘plateau', ‘slope', and ‘valley' field) in the Northern Guinea savanna (NGS) zone. Urea-N (45 kg N ha−1) was applied to all treatments on the ‘slope' and ‘valley' fields, while on the ‘plateau' field, plots were split into sub-plots with and without fertilizer N addition. Application of RP to Mucuna and Lablab led to site- and species-specific increases in grain yield, total N, and total P uptake of a subsequent maize crop. On the ‘plateau' and ‘valley' fields, maize grain yields, and total aboveground N and P uptake were significantly higher (1741 kg grains ha−1 on the ‘plateau' field and 910 kg grains ha−1 on the ‘valley' field) in the treatments following legumes treated with RP, compared to the treatments following legumes without RP addition. These increases were highest for the Mucuna treatment in both fields. On the ‘slope' field with high initial Olsen-P content application of RP to preceding legumes did not influence maize yield or N and P uptake. Improvements of maize yields on the ‘plateau' field were the results of an improvement in the soil P status after growing legumes supplied with RP, as maize did not respond to the addition of urea in the absence of RP addition to the preceding legumes. Recovery of RP-P by the maize varied between 3.1 and 5.8%. On all fields, legumes also improved the soil N status, giving average apparent legume N recoveries of 17% for Mucuna and 32% for Lablab. The results clearly show that soil fertility management in the NGS needs to take into consideration both N and P. The studied legume–maize rotations supplied with RP during the legume phase and minimal amounts of inorganic N during the maize phase are good examples of promising soil fertility management technologies alleviating N and P deficiencies. Recommendations need to be diversified following the position of the field on the toposequence and previous P application history.